Ban yue 半月 (The Half Moon Journal) Vol 2 No 14 (31 Mar, 1923) - (:unkn) unknown (發行者：Yuan Hanyun 袁寒雲，總發行所：Da dong shuju 大東書局)
A bimonthly literary magazine edited by Zhou Shoujuan 周瘦鵑, featuring fiction, topical articles, and entertainment features, published from September 1921 through November 1925.
Vol 2 No 14
Vol 2 No 14